Prosecutor's Professionalism in the Internal Investigation Process Eradication of Corruption (Study at the Aceh Besar District Prosecutor's Office) - Rijal, Ahsanur; Nuraeny, Henny; Suprijatna, Dadang; Darmika, Ika (Jurnal Pengabdian Nusantara, 2025)
The professionalism of prosecutors in the process of investigating corruption crimes is a crucial aspect in ensuring justice, legal certainty, and the effectiveness of corruption eradication. The Prosecutor's Office as a law enforcement agency has a strategic role in investigating corruption cases in accordance with the authority regulated in laws and regulations. This study aims to analyze the professionalism of prosecutors in investigating corruption crimes at the Aceh Besar District Prosecutor's Office, focusing on factors that affect the effectiveness of investigations, obstacles faced, and strategies to improve the quality of investigations. This study uses normative juridical and empirical juridical methods with a qualitative approach. Data was collected through literature studies and interviews with prosecutors in charge of investigating corruption cases. The results of the study show that the professionalism of prosecutors is influenced by technical competence, independence, and moral integrity. However, in practice, investigations often face obstacles such as political intervention, limited human resources, lack of use of digital forensic technology, and weak coordination between law enforcement agencies. To increase the effectiveness of investigations, strategic steps are needed such as increasing the capacity of prosecutors through continuous training, the application of digital technology in the collection of evidence, and strengthening cooperation between law enforcement agencies. With regulatory reform and more transparent supervision, it is hoped that efforts to eradicate corruption can run more optimally and contribute to a better justice system.